TINGKAT PENGETAHUAN MAHASISWA UNIVERSITAS TADULAKO TERHADAP SWAMEDIKASI PENYAKIT GASTRITIS - Ririen Hardani; Muhamad Rinaldhi Tandah; Chindy Bestari Rataba (Universitas Pahlawan, 2022)
Self-medication is carried out as an effort for patients to maintain and pay attention to their own health. Knowledge in self-medication of gastritis is important to have. It can support the use of drugs correctly and appropriately in choosing drugs because if the drug is used incorrectly it can cause the situation to become unfavorable. The purpose of the study was to determine the level of knowledge of students, use of drugs and sources of information on gastritis drugs and the relationship between age and sex factors on the level of knowledge of Tadulako University students in self-medication of gastritis. Type of research was a descriptive cross-sectional with a population of 38,702 a sample of 404 people by purposive sampling. The independent variables in this study were sociodemographic factors, while the dependent variable was the level of students' knowledge of gastritis self-medication. The data source used is primary data by filling out a questionnaire through Google Form. The data was analyzed by univariate and bivariate analysis, namely the chi-square test. A total of 83 respondents (20.5%) had a good level of knowledge, 112 (27.7%) were classified as moderate and 209 (51.7%) were quite. The use of gastritis drugs consumed was categorized as good with an average value of 85%, the source of drug information obtained was based on personal/family experience as much as 37% and there was no relationship between the level of knowledge of self-medication for gastritis of Tadulako University students with age (value 0.116 > 0.005) and gender (value 0.452 > 0.005). The level of knowledge was classified as good, the use of drugs is categorized as good and the dominant source of information is obtained based on personal/family use and there is no significant relationship between age and gender factors on the level of knowledge. Keywords : Gastritis, Tadulako University Students, Use Of Drug, Self-Medication, Level Of Knowledge